Illustrationen musikalischen Vergnügens. Die Bildrhetorik des 'Grand Divertissement royal' (1668) - Steigerwald, Jörn (Musik im Blick. Visuelle Perspektiven auf auditive Kulturen)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Fautes donjuanesques, remontrances galantes. Réflexions sur Le Festin de Pierre de Molière - Schlieper, Hendrik (Molière, dramaturge de la société de cour)

Idélic Approach in Enumerating Heisenberg Extensions - Klüners, Jürgen; Wang, Jiuya (La Matematica)

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Ursachen vorzeitiger Vertragslösungen im Spannungsfeld von statistischer Beschreibung und Praxis - Heisler, Dietmar; Lüttke, Daniela (Berufsbildung)

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Apocalypse Now? Endzeitphantasmen bei Wilhelm Genazino und Markus Orths - Süwolto, Leonie (Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren ‚Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller‘)